TikTok as a Cathartic Space Content Analysis of the @hendrabdrudy Account in Alleviating Work-Related Stress - Khatibah, Khatibah; Muktarruddin, Muktarruddin (Universitas Gadjah Mada, 2025)
This study analyzes how the TikTok account @hendrabdrudy functions as a cathartic space to alleviatework-related stress, particularly in the educational environment. Using a qualitative approach and content analysis techniques, this research explores key themes in the videos uploaded by Hendra Brudy, as well as audience responses reflected through comments, likes, and shares. The findings indicate that the use of humor, relatable personal narratives,and strong visual expressions are key elements in helping users manage stress. Additionally, social interactions in the comment sections reinforce TikTok’s role as a virtual community where individuals feel heard and supported. The Spiral of Silence theory is applied to analyze how social media facilitates individuals in speaking out about work-related stress that they may have previously suppressed. The results show that TikTok not only serves as an entertainment platform but also as an effective tool for supporting mental health in the workplace. This research contributes to theliterature on social media and mental health, offering practical insights for content creators and organizations on how to utilize social media as a means to foster a more supportive work environment.